FDP기반의 얼굴윤곽 정보를 이용한 2차원 얼굴영상 복원기법 - 조남철(Nam-Chul Cho); 이기동(Ki-Dong Lee) (한국콘텐츠학회 논문지, 6(6), 2006)
Nowadays, CCTV can be come across easily in public institutions, banks, and etc. These CCTV play very important roles for preventing many kinds of crimes and resolving those crime affairs. But in the case of recording image of a specific person far from the CCTV, the original image needs to be enlarged and recovered in order to identify the person more obviously. Interpolation is usually used for the enlargement and recovery of the image in this case. However, it has a certain limitation. As the magnification of enlargement is getting bigger, the quality of the original image can be worse. This paper uses FDP(Facial Definition Parameter) proposed by the MPEG-4 SNHC FBA group and introduces a new algorithm that uses face outline information of the original image based on the FDP, which makes it possible to recover better than the known methods until now. 오늘날 공공기관이나 은행 등 각종 범죄 예방 및 보안을 요하는 곳에서는 손쉽게 CCTV와 같은 감시용 카메라를 발견할 수 있다. 이런 감시용 카메라는 각종 범죄를 예방하고 범죄사건을 해결하는데 결정적인 단서를 제공해 주는 중요한 역할을 한다. 하지만 덜리 떨어져 있는 사람을 촬영하였을 경우, 그 사람이 누구인지 확인하기 위해서는 원 영상을 확대하여야만 하는데 영상을 확대하는 기법은 단순히 영상을 키우는 것이 중요한 것이 아니라 원 영상과 가깝게 양질로 확대 복원하는 것이 중요하다. 이처럼 영상의 확대 복원을 위해서 보간법이라는 기법을 이용하는데 지금까지 알려진 보간법으로는 확대 배율이 크면 클수록 식별이 불가능할 정도로 영상품질이 많이 떨어지게 된다. 따라서 본 논문에서는 MPEG-4 SNHC FBA그룹에서 표준화한 FDP(Facial Definition Parameter)를 이용하여 얼굴영상의 얼굴윤곽을 벡터화하여 복원함으로써 기존의 보간법으로 복원된 영상보다도 더 좋은 품질로 복원할 수 있는 새로운 방법을 제안한다.